The emerging self in psychotherapy with adults - Mackey, Richard A. (Bentham eBooks, 2009)
This Ebook focuses theoretically, empirically and practically on a concept of the self that includes neurobiological, psychological and social dimensions in psychotherapy with adults. The theoretical perspective on the self that is developed in the Ebook can be the basis for how a therapist may use himself/herself professionally in a therapeutic relationship. It is expected that the book will be of interest to many persons in this field.